2010
DOI: 10.1007/s00436-010-1985-9
|View full text |Cite
|
Sign up to set email alerts
|

Infection of non-encapsulated species of Trichinella ameliorates experimental autoimmune encephalomyelitis involving suppression of Th17 and Th1 response

Abstract: Epidemiological and experimental studies have indicated that helminth infections can ameliorate autoimmune diseases. The present study investigated the amelioration effect of the Trichinella pseudospiralis infection on experimental autoimmune encephalomyelitis (EAE), a T-cell-mediated autoimmune disease of central nervous system (CNS), and expression kinetics of Th17 and Th1 cytokine which play a crucial role in the pathogenesis of EAE. The results indicated that the infection of helminth T. pseudospiralis obv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 64 publications
1
44
0
Order By: Relevance
“…Trichinella infections have been found to down-regulate the inflammatory immunopathology caused by autoimmune diseases in various animal models such as experimental autoimmune encephalomyelitis (EAE) in rats [11], [43], [60], [61] and experimental colitis in mice [38], [39]. However, the mechanism or the molecules involved in this immunomodulation are not quite known.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Trichinella infections have been found to down-regulate the inflammatory immunopathology caused by autoimmune diseases in various animal models such as experimental autoimmune encephalomyelitis (EAE) in rats [11], [43], [60], [61] and experimental colitis in mice [38], [39]. However, the mechanism or the molecules involved in this immunomodulation are not quite known.…”
Section: Discussionmentioning
confidence: 99%
“…The ES proteins from T. spiralis muscle larvae (MES) have shown to be able to stimulate bone-marrow derived dendritic cells (DCs) to produce a mixed Th1/Th2 cytokine profile with the predominance of Th2 and regulatory cytokines [29]. Mice received T. spiralis MES simulated DCs significantly boosted Treg cells that secreted regulatory IL-10 and TGF-β cytokines [62], and decreased production of IFN-γ and IL-17 that leaded to the amelioration of experimental autoimmune encephalomyelitis [60], [61]. Except for MES, Trichinella AES was also able to inhibit pro-inflammatory cytokines and induce regulatory cytokines such as IL-10 and TGF-β via macrophage cells in vitro [29], [32], suggesting AES also plays similar roles in regulating immunological disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Sewell et al (2003), the intra-peritoneal injection of schistosome eggs protected mice from EAE, whereas La Flamme et al (2003), reported that a similar injection did not have protective effect. In general, a down-regulation of both Th17 and Th1 cytokine expression has been demonstrated (Walsh et al, 2009;Wu et al, 2010;Reyes et al, 2011) except in papers published before the emergence of the Th17 concept (Sewell et al, 2003;La Flamme et al, 2003). Regarding cellular involvement in the suppression, B cells highly expressing CD23 were shown to be responsible for EAE suppression in adoptive transfer experiments.…”
Section: Experimental Autoimmune Encephalomyelitis (Eae)mentioning
confidence: 99%
“…Moreover, Aranzamendi et al reported that Trichinella infection protected the host against allergic airway inflammation (8). It is obvious that Trichinella infection affects the host immune responses, but most studies regarding immunomodulatory actions by Trichinella were done using T. spiralis, and studies of immunomodulation by T. pseudospiralis are available in limited numbers only (9). As the immunomodulatory activity of T. pseudospiralis may be different from that of T. spiralis as mentioned above, it is necessary to make clear the mechanisms underlying the immunomodulation by T. pseudospiralis.…”
mentioning
confidence: 99%